Long-term outcomes and predictors of survival after cardiopulmonary resuscitation for in-hospital cardiac arrest in a tertiary care hospital in Thailand - Limpawattana P; Aungsakul W; Suraditnan C; Panitchote A; Patjanasoontorn B; Phunmanee A; Pittayawattanachai N (Dove Medical Press, 2018)
Panita Limpawattana,1 Wannaporn Aungsakul,2 Chomchanok Suraditnan,2 Anupol Panitchote,3 Boonsong Patjanasoontorn,3 Anakapong Phunmanee,3 Nittaya Pittayawattanachai4 1Division of Geriatric Medicine, Department of Internal Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 2Department of Internal Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 3Division of Critical Care, Department of Internal Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 4CPR Unit, Srinagarind Hospital, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Background: There are limited data available regarding long-term survival and its predictors in cases of in-hospital cardiac arrest (IHCA) in which patients receive cardiopulmonary resuscitation.Purpose: The objectives of this study were to determine the 1-year survival rates and predictors of survival after IHCA.Patients and methods: Data were retrospectively collected on all adult patients who were administered cardiopulmonary resuscitation from January 1, 2013 to December 31, 2014 in Srinagarind Hospital (Thailand). Clinical outcomes of interest and survival at discharge and 1 year after hospitalization were reviewed. Descriptive statistics and survival analysis were used to analyze the outcomes.Results: Of the 202 patients that were included, 48 (23.76%) were still alive at hospital discharge and 17 (about 8%) were still alive at 1 year post cardiac arrests. The 1-year survival rate for the cardiac arrest survivors post hospital discharge was 72.9%. Prearrest serum HCO3<20 meq/L, asystole, urine <800 cc/d, postarrest coma, and absence of pupillary reflex were predictors of death.Conclusion: Only 7.9% of patients with IHCA were alive 1 year following cardiac arrest. Prearrest serum HCO3<20 meq/L, asystole, urine <800 cc/d, postarrest coma, and absence of pupillary reflex were the independent factors that predicted long-term mortality. Keywords: developing country, IHCA, outcomes, predictors, survival